Demographic characteristics of stroke in a tertiary care hospital in Nepal - Dhungana, Krishna (Nepal Journal of Neuroscience, 2018)
Our aim is to find out the demographics of the patients with stroke who undergo in-patient rehabilitation in a tertiary care hospital setting. We also aim to find the frequency of different types of stroke and the frequency of stroke in different vascular territories. Using data collected prospectively over a period of 1 year, we studied 180 individuals admitted with stroke. The demographic features of patients with stroke were collected and analyzed. Stroke was broadly stratified into hemorrhagic and ischemic stroke. Furthermore, ischemic stroke was subdivided according to the vascular territories involved: anterior cerebral artery, middle cerebral artery (MCA), posterior cerebral artery, brain-stem, cerebellar, smallvessel strokes and stroke occurring in more than one vascular territory. The most common risk factor was hypertension which was present in 50% of patients. The most common ischemic stroke groups were MCA stroke (39.4%) and small vessel stroke (17.2%). The most common type of hemorrhage was basal ganglia hemorrhage which was present in 15% of patients. In regards with Western literature, patients with stroke in our setting also had similar risk factors. The proportion of hemorrhagic stroke in our country was higher than in the western world. A large proportion of patients were in the age group less than 65. However, the frequency of distribution of different types of stroke and frequency of stroke in different territories were similar.